Inheritance of productive tillering in F1 soft winter wheat using the short-statured variety Bilotserkivska napivkarlykova as the maternal parent (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Formulation of the problem. The growing demand for food under limited arable land resources and increasing impact of climatic factors necessitates the development of high-yielding and adaptive soft winter wheat varieties. Quantitative productivity traits are characterized by a complex polygenic nature and are strongly modified by environmental conditions, which complicates the prediction of their inheritance in hybrids. Therefore, studying the expression and inheritance patterns of productive tillering is of particular relevance for improving the efficiency of breeding programs and developing new genotypes with high yield potential and adaptability. Purpose. To determine the expression of productive tillering in parental forms and F₁ hybrids of soft winter wheat and to identify the type of inheritance when using the short-stemmed variety Bilotserkivska napivkarlykova as the maternal component in crosses. Methods. Under the conditions of the experimental field of the Educational and Production Center of Bila Tserkva National Agrarian University, eight hybrid combinations obtained from crossing varieties differing in plant height were studied over three years. Biometric analysis was conducted on an average sample of 25 plants in three replications. Results. The study revealed significant variability in productive tillering depending on the selected crossing combinations and year conditions. The lowest values of productive tillering in 2021 were caused by early cessation of autumn vegetation, very late resumption of spring vegetation, and insufficient precipitation in April. During 2019–2022, when the short-stemmed variety Bilotserkivska napivkarlykova was used as the maternal form, the predominant type of inheritance of productive tillering was positive overdominance, observed in 66.7% of hybrids with the degree of phenotypic dominance hp = 1.1–88.0. A stable expression of hypothetical and true heterosis over three years was found in the combinations Bilotserkivska napivkarlykova / Albatros odeskyi (Ht = 8.2–178.4%; Hbt = 0.7–127.4%), Bilotserkivska napivkarlykova / Vidrada (Ht = 18.5–133.3%; Hbt = 4.4–111.6%), and Bilotserkivska napivkarlykova / Pylypivka (Ht = 7.1–88.0%; Hbt = 4.7–70.5%). Conclusions. A significant influence of parental components on the formation of productive tillering, the degree of phenotypic dominance, and heterosis in F1 hybrids was established. The identified hybrid combinations with stable heterosis expression over three years have practical breeding value for effective trait recombination in subsequent generations.
Keywords: winter wheat; productivity; plant height; hybridization; inheritance; degree of phenotypic dominance; hypothetical heterosis; true heterosis